Investigation of the Relationship between Personality Traits of Intensive Care Nurses and Their Attitudes and Behaviours towards End-of-life Care - Fırat Demir; Cansu Polat Dünya; İlknur Özkan (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: End-of-life care is often provided by nurses in intensive care units, and enhancing the quality of patient care largely depends on personality traits. Aim: The study aimed to investigate the associations between the attitudes and practices of intensive care nurses toward end-of-life care and their personality traits. Method: This cross-sectional study involved 201 intensive care nurses. The Ten-item Personality Inventory and the Attitudes and Behaviors Towards End-of-Life Care Scale were used. Regression analysis and the independent samples t-test were used to analyze the data. Results: The nurses' average age was 29.90 ± 4.64 years. The highest-scoring personality traits were extroverted and willing, sympathetic and warm, and reliable and self-disciplined. Age was significantly associated with agreeableness (p = 0.043). Emotional stability scores were lower for nurses in anesthesia and reanimation units compared to other units (p = 0.004). The duration of working in the intensive care unit was inversely connected with extraversion (p = 0.023). The mean overall score for attitudes and behaviors about end-of-life care was 56.29 ± 5.62. No significant correlation was found between personality traits and the Attitudes and Behaviors towards the End-of-Life Care Scale. Conclusion: Age, the type of intensive care unit, and years of experience were associated with certain personality traits among nurses. Yet, no statistically significant correlation was discovered between personality characteristics, beliefs, and practices around end-of-life care